Revisiting Asset Pricing Puzzles in an Exchange Economy - Parlour, Christine A.; Stanton, Richard; Walden, Johan (Review of Financial Studies, 2011)
[We show that several well-known asset pricing puzzles are largely mitigated if we endow the representative agent with an arbitrarily small minimum consumption level. This allows us to solve the model for parameter values where the standard "Lucas tree" model is not defined. For these parameters, disasters become more important, and the market risk premium therefore higher, even though consumption is less risky. Our model yields reasonable risk premia, Sharpe ratios, and discount rates; excess price volatility; and a high market price-dividend ratio. We derive closed-form solutions for all variables of interest.]